2017
DOI: 10.1515/aiht-2017-68-2919
|View full text |Cite
|
Sign up to set email alerts
|

Can zinc supplementation ameliorate cadmium-induced alterations in the bioelement content in rabbits?

Abstract: The study was designed to investigate the influence of zinc (Zn) supplementation on cadmium-induced alterations in zinc, copper (Cu), and magnesium (Mg) status in rabbits. For this purpose, the concentrations of cadmium (Cd), Zn, Cu, and Mg were estimated in the blood, liver, kidney, and bone. The rabbits were divided in a control group, a Cd group-animals intoxicated orally with Cd (10 mg kg -1 bw, as aqueous solution of Cd-chloride), and a Cd+Zn group-animals intoxicated with the same dose of Cd and co-treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 50 publications
1
17
1
Order By: Relevance
“…Even though exposure to Pb and Cd has been shown to interfere with essential metals in many tissues (15,30,(51)(52)(53), our findings fail to confirm this in the rat brain. No visible interference in the brain was also reported by other similar studies (54,55).…”
Section: Discussioncontrasting
confidence: 99%
“…Even though exposure to Pb and Cd has been shown to interfere with essential metals in many tissues (15,30,(51)(52)(53), our findings fail to confirm this in the rat brain. No visible interference in the brain was also reported by other similar studies (54,55).…”
Section: Discussioncontrasting
confidence: 99%
“…This is supported by the fact that we measured lower serum values of Mg in all treated groups, with the most pronounced reduction in groups treated with Pb. Interaction between toxic metals and bioelements has been extensively studied by our research group and these studies confirmed many hypotheses; prolonged oral exposure to Cd significantly reduced Zn levels in blood and nine organs; Cd interferes with intestinal Mg absorption and affects its homeostasis; and Cd exposure results in negative effects on Mg, Zn, Cu, and even iron tissue levels [12,13,14,41,42,76,77].…”
Section: Discussionmentioning
confidence: 56%
“…The present body of knowledge suggests oxidative stress as one of the critical mechanisms of toxicity of both metals, even though neither of these metals is a Fenton’s metal [7,8,9,10]. Other possible mechanisms of toxicity are binding to oxygen, nitrogen, and sulphur ligands, which may affect numerous enzymes and proteins [7,11]; interaction with bioelements [12,13,14]; inhibition of apoptosis [15]; and changes in DNA structure and the inhibition of damaged DNA repair, which may lead to aberrant gene expression [16,17,18].…”
Section: Introductionmentioning
confidence: 99%
“…This conflicted finding was partly attributed to the observed higher Zn levels in the same group of patients and the relatively small sample size (65 participants). Indeed, Cd belongs to the same group of elements as zinc, and the number of common biological targets of the two metals abound [56][57][58][59][60]. The role of zinc in insulin regulation has been extensively examined [61][62][63].…”
Section: Insulin Resistance and Cadmium: Human Studiesmentioning
confidence: 99%